“DV Fatigue”: Work Stress and Officers’ Attitudes and Performance at Domestic and Family Violence Incidents - Maple, Emily (Violence against women, 2024)
A self-report instrument was created to measure stress, attitudes, and performance of domestic and family violence (DFV) first responders in an Australian state. DFV-related stress negatively impacted officers’ attitudes and self-assessed performance. Higher DFV stress was predicted by the frequency and severity of DFV incidents, and the absence of lived experience. Negative attitudes were predicted by a shorter length of service and lower severity, and poorer performance by a longer length of service and lower perceived social support. Males reported higher stress and poorer performance than females. The findings reveal systemic issues that inhibit effective police response, emphasizing the need to address negative attitudes and “DV fatigue.”